Surface plasmon resonance study on HIV-1 integrase strand transfer activity - Vaisocherová, Hana; Snásel, Jan; Springer, Tomás; Sípová, Hana; Rosenberg, Ivan; Stepánek, Josef; Homola, Jirí (Analytical and bioanalytical chemistry, 2009)
Understanding the molecular mechanism of HIV-1 integrase (IN) activity is critical to find functional inhibitors for an effective AIDS therapy. A robust, fast, and sensitive method for studying IN activity is required. In this work, an assay for real-time label-free monitoring of the IN activity based on surface plasmon resonance was developed. This assay enabled direct monitoring of the integration of a viral doubled-stranded (ds) DNA into the host genome. The strand transfer reaction was detected by using two different DNA targets: supercoiled plasmid (pUC 19) and short palindrome oligonucleotide. The effect of the length of the DNA target on the possibility to monitor the actual process of the strand transfer reaction is discussed. The surface density of integrated ds-DNA was determined. IN binding to the oligonucleotide complexes and model DNA triplexes in the presence of various divalent ions as metal cofactors was investigated as well. The assay developed can serve as an important analytical tool to search for potential strand transfer reaction inhibitors as well as for the study of compounds interfering with the binding of ds long terminal repeats-IN complexes with the host DNA.
Keywords: HIV-integrasa; Base Sequence; sekvence nukleotidů; DNA primery; Surface Plasmon Resonance; povrchová plasmonová rezonance; DNA Primers; HIV Integrase